Hubungan Resiliensi Terhadap Work Life Balance Pada Pekerja di Masa Pandemi Covid-19 - Istiqamah, St Hadjar Nurul; Ismail, Ismalandari (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
This study aims to determine the work life balance of workers during the pandemic. This type of research is a quantitative research with data collection techniques using resilience questionnaires and work life balance. The research respondents were 99 respondents who had an age range of 25-40 years. This research was conducted by distributing questionnaires via google form. The results of the study showed that there was a positive relationship between resilience and work life balance in workers during the Covid-19 pandemic. This relationship can be seen from the magnitude of the correlation or r between resilience and work life balance is 0.511 with a significance level or p of 0.000. This shows that the higher a person's resilience, the higher the work life balance of workers in the community and vice versa. Thus, the results obtained that workers who have high resilience can work well and have a balanced life between work and family.